The effect of stroboscopic vision on performance in a football specific assessment. Issue 4 (2nd October 2021) - Beavan, Adam; Hanke, Lars; Spielmann, Jan; Skorski, Sabrina; Mayer, Jan; Meyer, Tim; Fransen, Job
ABSTRACT: Purpose: This study aimed to investigate how restricted visual feedback affects performance in a football-specific skills assessment that incorporates the coupling of football a-specific perceptual information with football-specific motor actions. Methods: The Footbonaut is a 14x14m cage equipped with 8 ball dispensers and 64 targets measuring passing accuracy and time to complete each pass. Eighty-four amateur male participants (19.5 ± 5.4 years old; 13.1 ± 6.0 years experience) completed two sessions under two different visual conditions: stroboscopic and normal vision. Results: A linear regression revealed that performance under normal conditions was significantly associated (p < 0.001) with the performance decrement under stroboscopic vision conditions. Players were then subdivided into skilled (S; top 25%) and less-skilled (LS; bottom 25%) groups. Restricting visual feedback impacted the average time required to complete the passes in both S and LS groups equally (S: +0.18 s; LS: + 0.12 s; p = 0.385), yet S athletes' accuracy (−11.1%) was more heavily reduced under restricted visual conditions compared to their Normal condition; whereas the LS athletes' accuracy remained relatively unchanged (−1.9%). Conclusion: Therefore, stroboscopic vision may be used to induce performance errors during practice to stimulate larger training effects, particularly in more skilled players.